HUMOR STYLES, CREATIVITY AND LIFE SATISFACTION: A STUDY ON HIGH SCHOOL STUDENTS - Recep KOÇAK (Fırat University, 2019)
The main purpose of this study is to investigate the explanatory role of humor styles and creativity level of high school students on their life satisfaction level. Also it is investigated that there is a meaningful difference humor styles, creativity, academic achievement and life satisfaction of high school students according to their type of school, perceived income status and the mother's employment status. The research is a study done in the relational survey model, and has been carried out with 390 adolescent participants 201 female and 189 male students who are selected randomly among the 10th and 11th grade students, between 14-18 ages. In this study “Personal Demographic Information Sheet”, “Humor Styles Questionnaire”, “How creative are you?” and Multidimensional Students Life Satisfaction Scales were used to collect research data. In order to answer to research questions t-test, Pearson correlation, ANOVA and regression analyses were performed for data analysis. As a result of the analysis, it has been found that when the predictive power of the variables are taken into consideration, among the variables that make positive contribution to life satisfaction of students; participatory humor (ß =.17) comes first, self-defeating humor (ß = .15) comes second, aggressive humor style (ß=-.12), comes third, self enhancing humor style (ß=.12) comes fourth and creativity level’s comes (ß=-.11) last. According to the results of the regression analysis If the humor styles’ (participatory humor, self enhancing humor, aggressive humor and self-defeating) and creativity levels of students' taken together in terms of life satisfaction It is understood that there is a significant relationship between them (r=.34, P